544. PICKUP: Pneumonia in the Immunocompromised - Use of the Karius Test for Detection of Undiagnosed Pathogens. (15th December 2022) - Bergin, Stephen P; Chemaly, Roy F; Duttagupta, Radha; Bigelow, Robert; Dadwal, Sanjeet S; Hill, Joshua A; Lee, Yeon Joo; Haidar, Ghady; Luk, Alfred; Drelick, Alexander Christian; Chin-Hong, Peter V; Benamu, Esther; et al.
Abstract: Background: Pneumonia is the most common infectious cause of morbidity and excess mortality complicating hematopoietic cell transplantation (HCT) and treatment of hematologic malignancy. Standard bronchoscopic and noninvasive microbiologic testing identify causative pathogens in less than half of cases. The Karius Test, a plasma next-generation sequencing assay of microbial cell-free DNA, may improve diagnostic yield in these patients. Methods: Patients with active hematologic malignancy or recent HCT undergoing bronchoscopy for suspected pneumonia were prospectively enrolled in this observational study conducted at 10 United States medical centers. A panel of expert clinicians blinded to Karius Test results reviewed a standardized panel of microbiologic and molecular testing from bronchoalveolar lavage and blood samples for bacterial and fungal testing, nasopharyngeal swab for respiratory viral testing, imaging results, clinical documentation, and any additional microbiologic or molecular testing collected per usual standard of care to adjudicate a probable cause of pneumonia. The panel then adjudicated whether a probable cause of pneumonia or other clinically relevant infection was identified by the Karius Test. Results: Between January 3, 2020 and February 4, 2022, 257 patients were enrolled. A planned interim analysis of the first 69 sequentially enrolled patients in the per protocol population was conducted. An adjudicated probable cause of pneumonia was identified by standard care in 18/69 (26%) patients. The Karius Test identified an adjudicated probable cause of pneumonia in 10/51 (20%) patients when no cause of pneumonia was identified by standard care testing. The combination of standard care and the Karius Test together identified a probable cause of pneumonia in 28/69 (41%) patients. At least one additional pathogen adjudicated as a probable cause of pneumonia was identified by the Karius Test in 6/18 (33%) of patients with positive standard care testing. Conclusion: The Karius Test notably increased the probability of identifying a pathogenic cause of pneumonia among immunocompromised patients undergoing bronchoscopy. The additive diagnostic value of the Karius Test may significantly enhance management of this common condition. Disclosures: Roy F. Chemaly, MD/MPH, Karius: Advisor/Consultant|Karius: Grant/Research Support Radha Duttagupta, PhD, Karius Inc: Stocks/Bonds Sanjeet S. Dadwal, MD, FACP, FIDSA, AlloVir: Advisor/Consultant|AlloVir: Grant/Research Support|Ansun Biopharma: Grant/Research Support|Aseptiscope: Advisor/Consultant|Aseptiscope: Stocks/Bonds|Astellas: Speaker's Bureau|Cidara: Advisor/Consultant|Gilead: Grant/Research Support|Karius: Grant/Research Support|Merck: Advisor/Consultant|Merck: Grant/Research Support|Merck: Speaker's Bureau|Takeda: Speaker's Bureau Joshua A. Hill, MD, Allovir: Advisor/Consultant|Allovir: Grant/Research Support|Covance/CSL: Advisor/Consultant|CRISPR: Advisor/Consultant|Deverra: Grant/Research Support|Gilead: Grant/Research Support|Karius: Advisor/Consultant|Karius: Grant/Research Support|Merck: Grant/Research Support|Octapharma: Advisor/Consultant|OptumHealth: Advisor/Consultant|Oxford Immunotec: Grant/Research Support|Pfizer: Advisor/Consultant|Symbio: Advisor/Consultant|Takeda: Advisor/Consultant Ghady Haidar, MD, Karius, Allovir, and AstraZeneca: Grant/Research Support Alfred Luk, MD, Karius: Grant/Research Support Jamie Todd, MD, Altavant Sciences: Advisor/Consultant|AstraZeneca: Grant/Research Support|Boehringer Ingelheim: Grant/Research Support|CareDx: Grant/Research Support|Cellarity: Advisor/Consultant|Natera: Advisor/Consultant Genovefa Papanicolaou, MD, AlloVir: Board Member|AlloVir: Serve as member of DSMC|Amplyx: Board Member|Amplyx: Serve as member of DSMC|Astellas: Advisor/Consultant|Cidara: Advisor/Consultant|CSL Behring: Advisor/Consultant|Merck: Advisor/Consultant|Merck: Grant/Research Support|Merck: Investigator for Merck|MSD: Advisor/Consultant|Octapharma: Advisor/Consultant|Octapharma: Board Member|Octapharma: Serve as EAC member|Partners RX: Advisor/Consultant|SymBio: Advisor/Consultant|Takeda: Advisor/Consultant|Takeda: Grant/Research Support|Takeda: Investigator for Takeda|Vera: Board Member|Vera: Serve as member of DSMC Elena Nemirovich-Danchenko, MD PhD, Karius: Stocks/Bonds Mona Mughar, BS, Karius: Stocks/Bonds Sudeb Dalai, MD, Karius: Stocks/Bonds Sudeb Dalai, MD, Karius: Stocks/Bonds Yuen Cho, MS, CLS(CA-DPH), Karius: Stocks/Bonds Asim A. Ahmed, MD, Karius: Employee|Karius: Stocks/Bonds Desiree Hollemon, MSN, MPH, Karius: Stocks/Bonds David K. Hong, MD, Janssen Pharmaceutical Companies of Johnson & Johnson: Employee|Vir Biotechnology: Employee|Vir Biotechnology: Stocks/Bonds Marla Lay Vaughn, BS, MT(ASCP), Karius: Employee|Karius: Stocks/Bonds Tim Blauwkamp, PhD, Karius: Board Member|Karius: Ownership Interest Zivjena Vucetic, MD, Karius: Stocks/Bonds Rina Romano, BS, Karius Inc: Stocks/Bonds|Karius Inc: Stocks/Bonds Rina Romano, BS, Karius Inc: Stocks/Bonds|Karius Inc: Stocks/Bonds Rina Romano, BS, Karius Inc: Stocks/Bonds|Karius Inc: Stocks/Bonds Vance G. Fowler, Jr, MD, MHS, Affinergy: Grant/Research Support|Affinergy: Honoraria|Affinium: Honoraria|Amphliphi Biosciences: Honoraria|ArcBio: Stocks/Bonds|Basilea: Grant/Research Support|Basilea: Honoraria|Bayer: Honoraria|C3J: Honoraria|Cerexa/Forest/Actavis/Allergan: Grant/Research Support|Contrafect: Grant/Research Support|Contrafect: Honoraria|Cubist/Merck: Grant/Research Support|Debiopharm: Grant/Research Support|Deep Blue: Grant/Research Support|Destiny: Honoraria|Genentech: Grant/Research Support|Genentech: Honoraria|Integrated Biotherapeutics: Honoraria|Janssen: Grant/Research Support|Janssen: Honoraria|Karius: Grant/Research Support|Medicines Co.: Honoraria|MedImmune: Grant/Research Support|MedImmune: Honoraria|NIH: Grant/Research Support|Novartis: Grant/Research Support|Novartis: Honoraria|Pfizer: Grant/Research Support|Regeneron: Grant/Research Support|Regeneron: Honoraria|Sepsis diagnostics: Sepsis diagnostics patent pending|UpToDate: Royalties|Valanbio: Stocks/Bonds Thomas L. Holland, MD, Aridis: Advisor/Consultant|Lysovant: Advisor/Consultant.